Heat transfer enhancement in a parallel, finless heat exchanger using a longitudinal vortex generator, Part B: Experimental investigation on the performance of finless and fin-tube heat exchangers. (January 2019) - Li, Jiyang; Dang, Chaobin; Hihara, Eiji
Highlights: The heat transfer performance of the finless heat exchanger can be significantly enhanced by a longitudinal vortex generator. The heat transfer performance of finless heat exchanger can be significantly enhanced by a longitudinal vortex generator in dry, wet and frosting/defrosting conditions. The finless heat exchanger with a longitudinal vortex generator shows worse performance in dry conditions, but better in wet and frosting/defrosting conditions, while comparing with the fin-tube heat exchangers. Abstract: The air-side pressure drops and overall heat transfer coefficients of a finless heat exchanger with and without a vortex generator, as well as those of five all-aluminum parallel multi-port heat exchangers, were experimentally measured and compared under dry, wet, and frosting/defrosting conditions. The multi-port heat exchangers included three exchangers with louvered fins featuring fin pitches of 1.2 mm, 1.4 mm, and 1.6 mm, and two exchangers featuring slit fins with pitches of 1.2 mm and 1.4 mm. For the fin-tube heat exchangers, the effects of fin pitch and type on the air-side pressure drop and overall heat transfer performance were discussed. Under the dry condition, the heat transfer performance of a finless heat exchanger with a longitudinal vortex generator (LVG) is still approximately 40% less than that of a fin-tube heat exchanger. However, the pressure drop is similar. Under wet conditions, due to the excellent drainage performance of the finless heat exchanger, the heat transfer coefficient reached the same level. However, the pressure drop is lower. Under the frosting/defrosting condition, the heat transfer coefficient is similar, but the pressure drop is much lower. It only reaches 50 Pa at the end of each frosting period. Overall, the performance of a finless heat exchanger with a vortex generator is still lower than that of a fin-tube heat exchanger in dry conditions, but it demonstrates superiority in wet and frosting/defrosting conditions.